Enhancing electromechanical performance of extruded piezoresistive strain sensors: Study of TPU shore hardness effects - Imen Ayedi; Slim Naifar; Rajarajan Ramalingame; Mario Scholze; Martin Wagner; Olfa Kanoun (Journal of Materials Research and Technology, 2025)
Flexible strain sensors based on conductive thermoplastic elastomer composites have garnered significant attention for wearable electronics and soft robotics applications. Among the various material combinations, thermoplastic polyurethane (TPU) and multi-walled carbon nanotubes (MWCNTs) have emerged as promising candidates due to their processability and electromechanical properties. However, achieving the desired properties of these strain sensors requires careful selection of materials and meeting specific criteria. In this context, filament strain sensors have been developed by investigating different types of TPU with varying Shore hardnesses from 37 to 71, combined with MWCNTs as a conductive filler through an extrusion process. The fabrication process and characterization techniques are reported, guiding material selection when combining a TPU with a piezoresistive filler to create a soft, stretchable sensor. Characterization of the filament sensors by dynamic tensile testing shows that the sensors have a good piezoresistive response and can detect deformation accurately. Critical parameters such as drift, relaxation behavior, hysteresis and lifetime have extensively evaluated. It has seen that higher Shore hardness decreased the elongation at the point of fracture. In quasi-static cycle testing, Harder TPUs exhibited lower relaxation (4.34) and lower drift (3.72).